2010
DOI: 10.1053/j.seminoncol.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Regional Liver Therapy Using Oncolytic Virus to Target Hepatic Colorectal Metastases

Abstract: The mortality of colorectal carcinoma often results from the progression of metastatic disease, which is predominantly hepatic. Though recent advances in surgical, locoregional, and systemic therapies have yielded modest survival improvements, treatment of these aggressive lesions is limited to palliation for the vast majority of patients. Oncolytic viral therapy represents a promising novel therapeutic modality that has achieved tumor regression in several preclinical and clinical models. Evidence further sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…MSLN-targeted CAR T cells will be delivered through intrapleural catheters, an approach we developed to be the standard of care in managing patients with malignant pleural effusions (62). The regional administration of biological agents such as cytokines (63) and oncolytic virus (64) has been previously translated to the clinic with success. Our studies strongly support that regional CAR T cell administration to subjects with MPM will result in greater T cell anti-tumor potency with reduced T cell doses, owing in part to early CD4+ T cell activation and the systemic benefits that ensue.…”
Section: Discussionmentioning
confidence: 99%
“…MSLN-targeted CAR T cells will be delivered through intrapleural catheters, an approach we developed to be the standard of care in managing patients with malignant pleural effusions (62). The regional administration of biological agents such as cytokines (63) and oncolytic virus (64) has been previously translated to the clinic with success. Our studies strongly support that regional CAR T cell administration to subjects with MPM will result in greater T cell anti-tumor potency with reduced T cell doses, owing in part to early CD4+ T cell activation and the systemic benefits that ensue.…”
Section: Discussionmentioning
confidence: 99%
“…However, the safety of HAI administration of OVs is of great concern, particularly after the tragic incident of a fatal systemic inflammatory response syndrome in a patient following adenoviral gene transfer. 11 There have been a few preclinical and clinical studies on the safety of HAI of OVs, such as adenovirus, herpes simplex virus-1, and vesicular stomatitis virus (VSV), 12 – 14 but there is no safety information for the HAI administration of oncolytic poxvirus. In addition, it should be noted that >70% HCC patients have liver cirrhosis and/or other liver disorders; in a previous study conducted by Altomonte et al, the HAI administration of VSV showed no acute (up to 3 days) toxicity in rats with liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite the fact that recent progress in diagnosis and treatment has increased the number of patients who have been completely cured at an early stage of the disease, the prognosis for advanced forms of this cancer is still very poor, with treatment limited to palliation for the vast majority of patients. 2 The development of colorectal cancer (CRC) is a multistep process brought about by the accumulation of several genetic alterations, including chromosomal abnormality, gene mutations and epigenetic modifications involving several genes regulating proliferation, differentiation, apoptosis and angiogenesis. 3,4 Of the various genetic alterations, only a few are involved in cell growth and will lead to cancer development.…”
Section: Introductionmentioning
confidence: 99%